An Indirect Atomic Absorption Spectrometric Determination of Trifluoperazine Hydrochloride in Pharmaceutical Formulations Based on Chelate Formation with Palladium(II) - Ameen W. Qasim; Zuhair A. A. Khammas (E-Journal of Chemistry)
A new application of an indirect atomic absorption spectrometric (AAS) method was offered for the assay of low concentration of trifluoperazine hydrochloride (TFPH) in pure and pharmaceutical dosage form with good accuracy and precision. The method is depended on the formation of metal complex between the drug (TFPH) and palladium(II) to form orange-yellowish product extractable in organic solvent prior to its aspiration into an air-acetylene flame and indirectly determined by AAS. Using AA responses, all experimental parameters such as, pH, concentration of palladium, reaction time, extraction time and phase ratio which affect the complexation and extraction of TFPH-Pd(II), have been investigated. Under optimized conditions, linearity was observed in the range of 0.5-17 μg mL-1 with detection limit (S/N) of 0.038 μg mL-1, precision in range of 1.18-1.92%, accuracy as the %Erel of 2.4% and recoveries ranged from 101.7 to 104% with mean value of 102.4±0.135. The proposed method was applied for the determination of TFPH in the drug stelazine by both direct calibration and standard additions procedures and found to be 4.88 and 4.87 mg per unite, respectively compared with the stated value of 5 mg per unite. This method is also compared statistically with direct determination by using UV-Vis spectrophotometric technique which is preformed in our laboratory and found to be insignificant at 95% confidence level. All statistical calculations were implemented via the chemsoftware Minitab version 11.